Array Pattern Optimization for Steerable Circular Isotropic Antenna Array Using Cat Swarm Optimization Algorithm - Banerjee, Sudipta; Mandal, Durbadal (Wireless personal communications, 2018)
In this paper the steerable isotropic circular array antenna is designed for reducing the side lobe level (SLL) using evolutionary optimization technique. The optimization techniques particle swarm optimization and cat swarm optimization algorithm are used to reduce the SLL as well as to steer the main beam in specific direction. In this design of steerable circular arrays the amplitude excitations are optimized. Obtained results show that the maximum peak of SLL of the resultant patterns are as per requirement. This paper present a good performance in the array factor response and suppressed SLL for different number of array elements with different steering angle of the main beam using evolutionary optimization technique.